Sertoli-Leydig tumor in a 17-year-old girl: a case report - Robergeau, Fridjof S. G.; Massena, Larry M.; Nazaire, Maky-Kenson; Gilles, Bernard; Millien, Christophe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Sertoli-Leydig tumors of the ovary are rare. They can affect women in all age groups but are more frequent in the first three decades. No case of Sertoli-Leydig cells tumors has been reported in the Haitian literature. We present a case of a 17-year-old teenage who was seen in the outpatient clinic of the Mirebalais teaching hospital for: amenorrhea, change in voice and hair loss. After our evaluation and the completion of certain assessments, the clinical impression of a stromal and sexual cord tumor was retained, which guided us to perform a laparotomy. We conclude that in the management of this type of case, it is important to take into account the desire to preserve the patient's subsequent fertility and if there is one point that should not be overlooked, it is the psychosocial repercussions of the pathology before and after its treatment.